INNOVATIVE METHODS FOR ANALYSING HEART RHYTHM TURBULENCE IN PRECISION CARDIOLOGY - Amelina, T.M.; Malinevska-Biliichuk, O.V.; Tashchuk, M.V.; Tashchuk, V. (European Science, 2025)
An analysis of quantitative ECG indicators of 32 patients with ventricular arrhythmias was performed using a formula developed to calculate heart rate turbulence indicators (HRTO and HRTS) of Holter ECG monitoring with assessment of heart rate variability